Wetting a superomniphobic porous system. Issue 42 (18th October 2019) - Cimadoro, J.; Ribba, L.; Goyanes, S.; Cerda, E.
Abstract : We study experimentally and theoretically the critical pressure needed to move a liquid through a network of pores and show that, for small aperture size, wetting and leaking are typical first-order transitions, with a singular behavior at the omniphobic/omniphilic limit. Abstract : While important research has been focused on developing surfaces that do not wet, some textures with high-wetting resistance are familiar in other applications in which the opposite is needed. A multivalued surface, common in most fabrics or meshes, allows the invading gas–liquid interface to support relatively high imposed pressures and plays a key role in producing topographic elements that avoid wetting. Here we study experimentally and theoretically the critical pressure needed to move a liquid through a network of pores and show that, for small aperture size, wetting and leaking are typical first-order transitions, with a singular behavior at the omniphobic/omniphilic limit ( θ c = π/2).